Correlation of lipid and glycaemic profile with oxidative stress in the elderly with or without nontransmissible chronic diseases (Research, Society and Development, 2020)
Objectives: This study set out to determine whether there are any correlations between lipid and glucose levels and oxidative stress presented by elderly patients with and without nontransmissible chronic diseases (NTCDs). Methods: Serum biochemical concentrations of lipoproteins, glucose and oxidative stress markers (malondialdehyde and nitric oxide) were determined in 44 elderly patients (22 elderly people without NTCDs and 22 elderly people with NTCDs), aged between 60 and 81 years old. Results: The elderly people with NTCDs showed higher LDL concentrations, glucose, and oxidative stress markers than those without NTCDs. There was a positive and significant correlation between the levels of malondialdehyde with the abnormal lipid profile of the elderly without NTCDs and hyperglycaemia presented by elderly people with NTCDs. The total trolox equivalent antioxidant capacity had a negative correlation with the levels of malondialdehyde in the elderly without NTCDs. Another negative correlation was observed between the levels of nitric oxide and malondialdehyde in elderly people with NTCDs. Conclusion: Once oxidative stress and abnormal lipid profile have occurred in both groups, it is suggested that the hyperglycemia present in the group with chronic diseases has been determinant for the increase of the oxidative stress found in this group.